Equity Interest Scheme’s Compatibility with the UNCLOS 1982’s Common Heritage of Mankind Principle - Merdekawati, Agustina; Triatmodjo, Marsudi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
The Mining Code Exploration for polymetallic sulphides and cobalt-rich ferromanganese crusts provide options for exploration contractors to offer an equity interest in a joint venture with Enterprise. UNCLOS 1982 has never regulated the existence of such a scheme as a substitute for the obligation to submit reserved areas at the exploration stage. The presence of the equity interest scheme raises questions on its compatibility with the Common Heritage of Mankind (CHM) principle, especially with the aspect of equitable benefits sharing (EBS) to all mankind. This study aimed to assess the compatibility of the equity interest scheme with the CHM principle. The study was conducted normatively by analyzing equity interest scheme implementation associated with the norms in the CHM principle and UNCLOS 1982. The results showed that the equity interest scheme is compatible with the EBS aspects in the CHM principle by presenting the optimization of financial benefits for all mankind. The implementation of the equity interest scheme, even though it is contrary to the provisions of Annex III Article 1982, is a form of subsequent practice accepted by state parties. This study recommends that the relevant stakeholders reconsider the involvement of the Enterprise in the equity interest scheme based on financing efficiency.